Gender Dynamics in Crowdfunding (Kickstarter): Evidence on Entrepreneurs, Backers, and Taste-Based Discrimination - Gafni, Hadar; Marom, Dan; Robb, Alicia; Sade, Orly (Review of Finance, 2021)
Abstract This study focuses on the launch phase of the leading reward-based crowdfunding market—Kickstarter. It documents the behavior of male and female entrepreneurs in raising early stage capital. We find that women share as entrepreneurs in the platform (34.7%) does not equal to their share in the overall population, and they are concentrated in stereotyped sectors, both as entrepreneurs and as backers. We also find that women do not set lower funding goals than men, they enjoy higher rates of success than men, even after controlling for project categories and funding goals, and that backers of both genders have a tendency to fund entrepreneurs of their own gender. Our survey of Kickstarter backers finds evidence of taste-based discrimination by male backers.